Ectopia lentis et pupillae - Marcio,Fernanda (2011)
The Ectopia lentis et pupillae is a rare genetic syndrome, congenital, autosomal recessive with variable expression, characterized by ectopia of the lens and the pupil, usually bilateral and symmetrical, but without systemic manifestations. The pathogenesis of this anomaly is still unknown, but there are theories that the change is mesodermal, neuroectodermal, combined or mechanical. This article presents a clinical case of a patient with ectopia lentis et pupillae, describing its clinical and genetic aspects, secondary ocular complications and differential diagnosis.